Developing Effective Physical Fitness Testing Standards for Pre Service Physical Educators - Kory Hill; Roland Thornburg (Networks: An Online Journal for Teacher Research, 2016)
Physical educators are often held to a higher standard of physical fitness. The ability to effectively convey the importance of physical fitness may depend upon the ability to appear physically fit. The ability to perform at a minimal level of proficiency on fitness tests was deemed important by the faculty of one physical education teacher education program (PETE). In an action research evaluation, the faculty examined standards presented in the literature, as well as questionnaire responses by students, to develop reasonable passing scores for physical education majors. Results indicated the students are receptive to minimal standards and the initial standards are achievable by most students in the PETE program.
Keywords: higher education; action research; physical education; fitness testing